Prihodnost miselnih eksperimentov - Šetar, Niko (Analiza (Ljubljana), 2021)
The paper addresses the questions of current (contemporary) and future use of thought experiments as a method of scientific research. To do so we must first address the overall validity of thought experiments, which is done by examining criticisms that aim to discredit thought experiments' scientific and epistemic value and overviewing responses to those criticisms as well as other defences in favour of thought experiments, such as the notion of anti-fallacies. After doing so, we compare thought experiments to other research methods, namely empirical experiments and computer models. We will argue that empirical experiments are faulty to at least the same degree as thought experiments, while the latter have certain procedural properties that allow them to provide data that is inaccessible by the other two methods and therefore retain their status as a valid, independent research method.
Keywords: computer modelling; empirical experiments; empirični eksperimenti; miselni eksperimenti; računalniško modeliranje; raziskovalne metode; research methods; thought experiments